Offshoring of Medium-skill Jobs, Polarization, and Productivity Effect: Implications for Wages and Low-skill Unemployment - Ehsan Vallizadeh; Joan Muysken; Thomas Ziesemer (Maastricht Economic and social Research institute on Innovation and Technology (UNU-MERIT), 2015)
We examine the effects of endogenous offshoring on cost-efficiency, wages and unemployment in a taskassignment model with skill heterogeneity. Exact conditions for the following insights are derived. The distributional effect of offshoring (high-) low-skill-intensive tasks is similar to (unskilled-) skill-biased technology changes, while offshoring medium-skill-intensive tasks induces wage polarization. Offshoring improves cost-efficiency through international task reallocation and puts a downward pressure on all wages through domestic skill-task reallocation. If elasticities of task substitution are low (high), the downward pressure on wages in neighboring skill segments is low (high) with a net effect of higher (lower) wages and employment.
Keywords: F16; F66; J21; J24; J64; 330; Task Assignment; Offshoring; Skills; Cost-efficiency Effect; Equilibrium Unemployment